Analisis Penggunaan Bahasa Daerah Dayak Kebahan Sebagai Bahasa Pengantar Dalam Pembelajaran Bahasa Indonesia - Susanti, Rosi; Nugraha, Asep Eka; Saputri, Linda Dwi (STKIP Melawi, 2024)
Abstract: The aim of the research is to analyze the causes and overcome the use of the Dayak Kebahan regional language as the language of instruction in Indonesian language learning. The research method is qualitative with a descriptive approach, descriptive research type. Research subjects were fourth grade teachers and fourth grade students. Data collection techniques use interviews and documentation. The results of the research show: (1) Problems with using regional languages in Indonesian language learning are difficulty remembering, understanding, applying, analyzing information, difficulty conveying conversations, misunderstanding regional languages, non-standard words, sentences mixed with regional languages, inappropriate content, inadequate understanding, diction and sentence structure are less precise, lack of understanding of punctuation. (2) The causal factors are students' lack of focus, not paying attention, no recording media available, lack of confidence, lack of focus, accustomed to using regional languages, lack of learning (3) Overcoming the problem of using regional languages in Indonesian language learning, namely being more focused, repeating learning until you understand, practice analyzing, using interesting media, practicing, understanding the content better, changing habits, speaking in front of the class, introducing yourself, asking questions and answers with friends, telling stories about experiences, telling pictures, reading regularly, reading five minutes before learning, providing motivation and books, discussions, presentations and observations.Keywords : Knowledge, Local Language, Dayak Kebahan, Indonesian Language Learning.Â Abstrak: Tujuan penelitian yaitu menganalisis penyebab dan mengatasi penggunaan bahasa daerah Dayak Kebahan sebagai bahasa pengantar dalam pembelajaran bahasa Indonesia. Metode penelitian yaitu kualitatif dengan pendekatan deskriptif, jenis penelitian deskriptif. Subjek penelitian guru kelas IV dan siswa kelas IV. Teknik pengumpulan data menggunakan wawancara dan dokumentasi. Hasil penelitian menunjukan: (1) Masalah penggunaan bahasa daerah dalam pembelajaran bahasa Indonesia yaitu sulit mengingat, memahami, menerapkan, menganalisis informasi, sulit menyampaikan pembicaraan, keliru bahasa daerah, kata tidak baku, kalimat bercampur bahasa daerah, kandungan isi kurang tepat, kurang memahami, diksi dan struktur kalimat kurang tepat, kurang memahami tanda baca. (2) Faktor penyebabnya yaitu siswa kurang fokus, tidak memperhatikan, tidak tersedia media rekaman, kurang percaya diri, kurang fokus, terbiasa menggunakan bahasa daerah, kurang berlajar (3) Mengatasi masalah penggunaan bahasa daerah dalam pembelajaran bahasa Indonesia yaitu lebih fokus, mengulang pembelajaran sampai paham, latihan menganalisis, menggunakan media menarik, berlatih, lebih memahami isi, merubah kebiasaan,Â berbicara di depan kelas, memperkenalkan diri, tanya jawab dengan teman, bercerita pengalaman, menceritakan gambar, rutin membaca, membaca lima menit sebelum pembelajaran, memberikan motivasi dan buku, diskusi, presentasi serta pengamatan.Kata Kunci : Penggunaan, Bahasa Daerah, Dayak Kebahan, Pembelajaran Bahasa Indonesia.